Educação com/para a mídia televisiva: uma experiência a partir de telejornais na escola - Ribeiro, Daniele Ferreira (2015)
Qualitative study with a descriptive and interventionist nature, also classified as an action research developed within the teaching practice. We aimed at developing a literacy project carried out with a group of 24 students from the 9th grade in a public school of Campina Grande. It started from the assumption that the participating students were immature regarding the television media, so we wanted to contribute for the formation of more critical readers, acting with the perspective of the social use of reading and writing. Therefore, we proposed the discussion and the production of two television news programs of different profiles, based on local TV news of greatest interest from the participating students, namely: "JPB", aired by Paraíba TV, an affiliate of Rede Globo; "A Patrulha da Cidade" aired by Borborema TV, SBT affiliate; and "Correio Verdade", aired by Correio TV, Rede Record affiliated. The study was based on authors such as Fischer (2006), Prado (2005), Setton (2011), Tinoco (2008) and Belloni (2012), involving field discussions of media-education and the pedagogy of projects, specifically literacy projects, considering the need of approaching the subject in schools and the range of utilization possibilities that favor the construction of knowledge related to students’ experience inside and outside the school environment. As a result, it is possible to do the following highlights: 1) students involved have shown progress in looking at the television, questioning the content presented by it, understanding the messages conveyed, from a different perspective, questioning the impartiality, the objectives, the target audience and the language used by the programs, paying attention to the interests of each; 2) the teacher is an indispensable professional in the intermediation of the learning process, with the use of media; 3) media-education is a valid choice when one intends to promote learning situations based on the actual use of reading and writing, i.e., with and through the use of literacy projects. The work with media-education is becoming more popular in classrooms, but much remains to be done, if the goal is to make sense of learning beyond the school environment.